Uji Adaptasi Tiga Varietas Bawang Merah (Allium cepa L. Aggregatum group ) pada Tanah Masam - ANDRIANI, DEWI; Jekki Irawan; Mawaddah Putri Arisma Siregar; Tsamarah Nur Rahmah; Mayasari (Jurnal Hortikultura Indonesia, 2025)
Shallot (Allium cepa var. aggregatum) is a high-value horticultural crop with significant economic importance in the culinary, health, and industrial sectors. The increasing market demand has driven eJorts to develop varieties that are adaptive to diverse environmental conditions. Of the more than 20 shallot varieties cultivated in Indonesia, only a few are capable of adapting to acidic soils. This study aimed to evaluate the adaptive capacity of three shallot varieties (Bima Brebes, Sanren, and Lokananta) in acidic soil conditions. The experiment was conducted on acidic soil using a non-factorial randomized complete block design (RCBD) with 9 replications, resulting in 27 experimental units. The results showed that all three varieties were able to grow on regosol soil with a soil pH value of 4.60 and significant differences were observed among the varieties for most growth parameters. Bima Brebes exhibited the highest performance at the final observation, with a plant height of 28.21 cm, 43.07 leaves, 9.69 tillers, 10.62 bulbs, 31.29 g bulb weight per clump, 40.96 g fresh bulb weight per plant, and 3.62 g dry bulb weight per plant. These findings suggest that Bima Brebes has strong potential as a superior variety for sustainable optimization of acidic soils. Keywords: Adaptation, Bima Brebes, Lokananta, Sanren